2011
DOI: 10.4104/pcrj.2011.00070
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering sex-based stereotypes of COPD

Abstract: Chronic obstructive pulmonary disease (COPD) has historically been considered a disease of older, white, male smokers, as illustrated in Frank Netter's classic images of the 'pink puffer' and 'blue bloater'. However, women may be more susceptible to COPD than men, and the disease course may be reflective of that increased susceptibility. From a review of epidemiological data of COPD, we found differences in the way men and women present with COPD symptoms, a bias in the way COPD symptoms are treated in men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 92 publications
2
26
0
1
Order By: Relevance
“…Extensive studies have shown that females have more severe symptoms compared to males, despite a shorter smoking history and a similar degree of obstruction and emphysema 26. Several underlying molecular reasons for this could be proposed as previously reported while analyzing BAL-cell proteome from the same cohort 17…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Extensive studies have shown that females have more severe symptoms compared to males, despite a shorter smoking history and a similar degree of obstruction and emphysema 26. Several underlying molecular reasons for this could be proposed as previously reported while analyzing BAL-cell proteome from the same cohort 17…”
Section: Discussionmentioning
confidence: 66%
“…More respiratory symptoms and deteriorating lung function are reported for post-menopausal females, and a protective role for estrogen in the development of COPD has been proposed 26. Among others, it has been shown to stimulate the expansion of CD4 + CD25 + T regulatory cells33 important for controlling inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Although COPD has historically been considered a disease of male smokers, it now clearly impacts on both sexes. 4 As Ohar, Fromer, & Donohue point out in this helpful review, 5 the paradigm of COPD is changing from a male-predominant two-category disorder, to a disorder characterised by multiple co-morbidities with a growing female prevalence.…”
Section: Commentarymentioning
confidence: 99%
“…This review 5 highlights key research areas in COPD where sex and gender stereotypes can be challenged -including disease susceptibility, symptoms, treatment, prognosis, and diagnosis. Although biological determinants of sex and age differences in airway behaviour (dimensional, immunological, and hormonal) have been known for many years, 6 there are still major gaps in our knowledge about COPD phenotypes.…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation